2004
DOI: 10.1002/cne.20136
|View full text |Cite
|
Sign up to set email alerts
|

Distinct expression of phosphorylated N‐methyl‐D‐aspartate receptor NR1 subunits by projection neurons and interneurons in the striatum of normal and amphetamine‐treated rats

Abstract: N-methyl-D-aspartate (NMDA) receptors are heteromeric assemblies of subunits (NR1 and NR2A-D), and are enriched in the striatum. Receptor phosphorylation has recently been demonstrated on the NR1 subunit at three serine residues, 897, 896, and 890, which appear to correspond to the level of receptor activity. In this study, expression of phospho-specific NR1 subunits at serine 897 (pNR1S897), serine 896 (pNR1S896), or serine 890 (pNR1S890) in neurochemically identified neurons of the adult rat striatum was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…For example, it has been demonstrated that acute administration of the psychostimulant, amphetamine, causes an increase in the phosphorylation of the N-methyl-D-aspartate receptor NR1 subunit at serine 890 and 896, but not serine 897 in the brain52. As depicted in Figure 5A and 5B, two different proteins, heterogeneous nuclear ribonucleoprotein C (hnRNP C) and methyl-CpG-binding protein 2 (MeCP2), exhibited distinct abundance distribution patterns of phosphorylation at different residues.…”
Section: Resultsmentioning
confidence: 99%
“…For example, it has been demonstrated that acute administration of the psychostimulant, amphetamine, causes an increase in the phosphorylation of the N-methyl-D-aspartate receptor NR1 subunit at serine 890 and 896, but not serine 897 in the brain52. As depicted in Figure 5A and 5B, two different proteins, heterogeneous nuclear ribonucleoprotein C (hnRNP C) and methyl-CpG-binding protein 2 (MeCP2), exhibited distinct abundance distribution patterns of phosphorylation at different residues.…”
Section: Resultsmentioning
confidence: 99%
“…In the single-labeling study, quantifications of immunoreactivity were carried out by counting the total numbers and determining the relative intensities of neurons which were immunoreactive to pNR1S897 in different areas as follows: (i) five selected areas [dorsolateral (DL), dorsomedial (DM), ventrolateral (VL), ventromedial (VM), and central subdivisions] in the dorsal striatum (namely CPu) [22] (see fig. 1 A); (ii) the ventral striatum (namely NAc) histochemically subdivided into a core region and a shell region for measurement [33] (see fig.…”
Section: Digital Image Analyses and Statisticsmentioning
confidence: 99%
“…NR1 shows phosphorylation at three distinct serine sites (897, 896, and 890) in the carboxyl tail region (intracellular domain). The previous study found that phosphorylated NR1 at serine 897 (pNR1S897) was expressed in the brains of the normal rats at the highest level amid three phosphorylated NR1 subunits (pNR1S897, pNR1S896, pNR1S890) [22] . It is an appropriate way to investigate the phosphorylation of NR1 serine 897 following the repeated drug exposure [22] , but the phosphorylation status of the NR1 has not been measured in the major regions (VTA and striatum) of reward system after chronic drug exposure.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Subcellular localization and phosphorylation state of NR1 could determine properties of NMDA receptors [15]. Within NR1, phosphorylation by protein kinase C (PKC) and protein kinase A (PKA) occurs on serine residues 890 and 896 (S890 and S896) and serine 897 (S897), respectively, in the carboxy tail region of the protein [16,17]. NMDAelicited currents are enhanced by activation of PKC and PKA.…”
Section: Introductionmentioning
confidence: 99%